IMPLEMENTATION OF LEARNING ENVIRONMENTAL POLLUTION MATTER WITH THE SSI-BASED EMODULE TO IMPROVE STUDENTS’ ENVIRONMENTAL LITERACY - Lestari, Suci Putri; Permana, Irvan; Rachman, Indriyani; Yayoi, Kodama (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2024)
This study aims to analyze the level of environmental literacy of students after using e-modules based on Socio Scientific Issues (SSI) on students' environmental pollution material through a survey method. The sample of this study was 26 students of MTs Yasti 1 Sukabumi. Data collection techniques were carried out using environmental literacy instruments adapted from Middle Schools Environmental Literacy Survey/Instrument (MSELS/I) questions made by NELA with modifications according to the context of environmental pollution. Data acquisition was transformed and interpreted using the NELA transformation method.The results showed that the SSI-based environmental literacy e-module was feasible to use in terms of feasibility (content, presentation and language), in terms of suitability for SSI and in terms of media with a percentage of 88%, 84% and 89% respectively. The CVI results related to the feasibility of the e-module are 0.995 (Valid). Learning using the SSI-based environmental pollution e-module can improve students' environmental literacy in the moderate category with an average N-Gain score of environmental literacy of 0.58. Student response to the SSI-based environmental pollution e-module is very good with an average percentage score of 91%. This research concludes that there is an increase in students' environmental literacy after using Socio Scientific Issues (SSI) based e-modules.